The Digital Disruption of Traditional Equilibrium: Analyzing the Impact of E-commerce and Social Commerce on Demand Supply Dynamics for Electronics in Makassar - Imran Musa, Chalid (Economics and Business Journal (ECBIS), 2025)
This research is based on the imbalance between demand and supply that often occurs in the consumer goods market in Makassar, which causes price changes and market instability. This study is unique in a local context by emphasizing the real interaction between demand and supply as a factor that affects the market balance at the regional level. The purpose of this study is to investigate the impact of demand and supply on the balance of the consumer goods market in Makassar. This study adopts a quantitative approach by using primary data from 250 respondents, consisting of 200 consumers and 50 traders with questions using a five-point Likert scale. Data analysis is carried out with multiple linear regression using SPSS version 25, as well as involving validity testing, reliability and classic assumption testing. Research findings show that the demand and supply variables have a positive and significant effect on the market balance with an Adjusted R² of 0.285. Together, the two variables explain 28.5% variation in market balance. This result shows that the increase in demand and the availability of the supply of consumer goods are the key to maintaining price stability in the local market.